(NzYBKAQ TWERDX (B:s (N~TO TAKOE ZEMLETRQSENIE I KAK K NEMU PODGOTOWITXSQ (B/s - (NgIR(B, (NdVEJMS s; (N{AH(B, (NhORE[ ~(B.s; (N{EBALIN(B, (Nn(B.(Nw(B.s ((NmOSKWA (B:s (NmIR(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 212-213 (28 (NNAZW(B.)s
(NuKAZ(B.: (NS(B. 218-220s
Keywords: (NzEMLETRQSENIQs; (NsEJSMOSTOJKOE STROITELXSTWOs